FREQUENCY OF THIRD MOLAR PATHOLOGY: INNOVATIVE CAUSES, SYMPTOMS AND TREATMENT OPTIONS - Dorin Ioan Cocoș; Kamel Earar; Sorana Maria Bucur; Mariana Păcurar; Mihaela Mariș; Izabela Diana Cocoș; Carmen Galea (Romanian Society of Oral Rehabilitation, 2023)
This study aims to present the frequency of pathology at the level of molars of the mind, this pathology can have a multitude of local and general factors, but the most common rate of the inclusion of the molar of the mind following research seems to be characterized by the presence of local factors. One of the most common complications is the impact, ie the inability of the mind molars to erupt on the dental arch. Treatment for the pathology of the mind molars may include observation, extraction, administration of antibiotics, oral surgery, correct orthodontic treatment, or oral hygiene, depending on the nature and severity of the problem. Nanotechnology in the scientific world is a new current, and in dentistry, new branches are already sketched: the nanodiagnotic (cancers diagnosis), the nanoprevention (nanocapsule toothpaste), nanotrataments (odontology, pedodontics, orthodontics, endodontics, surgical treatments, periodontal diseases). Nanomaterials can be simple solutions for solving complex dental problems and can represent the next generation in terms of dental materials development technology.